Cheating in chess: a call for an integrated disciplinary regulation - Zaksaitė, Salomėja (Kriminologijos studijos, 2020)
This article examines recent regulation in the sport of chess with a focus on cheating. On the one hand, disciplinary law in chess could be considered relatively underdeveloped compared with other sports. On the other hand, however, this kind of ‘underdevelopment’ might be appropriate since chess governing bodies have not yet introduced interventionist rules. These two interacting perspectives shape the aim and the objectives of legal research designed to protect the chess community from cheating by suggesting adequate disciplinary measures. The analysis focuses mainly on two forms of cheating: computer-assisted cheating and match-fixing. The broad concept of cheating and relatively young legal regulation in an under-researched sport call for interdisciplinary analysis, therefore, knowledge of sports law, human rights as well as criminology is applied.